Factbook on the Philippine regions. (Pasig City Infoquest Co., 1995)
The Factbook on the Philippine regions contains facts and figures on the country's 12 regions. The presentation is in table format. Each region contains maps and discussed its demographic profile such as its economy, social sciences and even infrastructure. At the end of the book is the summary of regional statistics.
Keywords: Philippines -- Regions -- Statistics